A method for reducing the activation energy of wind turbine blade low-temperature pyrolysis high-efficiency dissociation

CN122999646APending Publication Date: 2026-10-30NANCHANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611387113.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0006]针对上述现有技术存在的问题之一,本发明提供了一种降低活化能的风电叶片低温热解高效解离方法,解决传统热解活化能高、温度高、纤维损伤大、结焦严重和回收率低的问题

Benefits of technology

本发明改性羟基磷灰石固体催化剂孔道内部负载二价锰离子、镧离子活性位点,改性羟基磷灰石固体催化剂依靠表面酸碱活性位点选择性催化断裂环氧树脂交联网络C-N键、C-O醚键,降低化学键断裂反应势垒;复合含磷活化助剂受热分解释放含磷自由基活性中间体,含磷自由基活性中间体捕获树脂热解过程生成大分子自由基,抑制大分子链段二次交联生成致密热解残炭;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999646A_ABST
    Figure CN122999646A_ABST
Patent Text Reader

Abstract

The application discloses a kind of wind power blade low-temperature pyrolysis high-efficiency dissociation methods for reducing activation energy, it is related to low-temperature pyrolysis field, including S1, pretreatment process;S2, catalytic activation impregnation process;S3, preheating exhaust process;S4, subsection gradient low-temperature pyrolysis dissociation process;S5, in-situ carbon removal process in furnace;S6, inert atmosphere cooling and discharging process;The modified hydroxyapatite solid catalyst channel inside of the application is loaded with divalent manganese ion, lanthanum ion active site, modified hydroxyapatite solid catalyst relies on surface acid-base active site to selectively catalyze the fracture epoxy resin crosslinking network C-N bond, C-O ether bond, reduces chemical bond fracture reaction barrier;Composite phosphorus-containing activation aids are decomposed to release phosphorus-containing free radical active intermediates by heat, and the phosphorus-containing free radical active intermediates capture macromolecular free radicals generated in the process of resin pyrolysis, to inhibit the secondary crosslinking of macromolecular chain segments to generate dense pyrolysis residual carbon.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of low-temperature pyrolysis technology, and more specifically to a low-temperature pyrolysis method for efficient dissociation of wind turbine blades that reduces activation energy. Background Technology

[0002] Wind turbine blades are mainly made of epoxy resin impregnated glass fiber composites, with a service life of about 20 years. As the installed capacity of wind power in China increases year by year, a large number of retired wind turbine blades are entering the scrapping stage. The composite matrix of wind turbine blades is amine-cured bisphenol A type epoxy resin, which forms a dense and stable three-dimensional cross-linked network structure after curing. The material has high chemical stability and is difficult to degrade. Conventional landfill and incineration methods easily lead to waste of land resources and secondary air pollution. Therefore, pyrolysis dissociation technology has become the mainstream treatment method for the resource recycling of retired wind turbine blades.

[0003] Existing traditional wind turbine blade pyrolysis processes mostly adopt high-temperature inert pyrolysis mode, with conventional pyrolysis temperatures needing to reach 520℃-580℃ and holding times needing to be maintained for 120min-180min. The apparent activation energy of epoxy resin matrix pyrolysis is generally in the range of 142kJ / mol-168kJ / mol. This type of high-temperature pyrolysis process has many technical defects: First, the high-temperature pyrolysis environment easily leads to high-temperature crystallization, surface etching, and microcrack propagation on the surface of glass fibers, resulting in a significant decrease in the mechanical properties of recycled glass fibers. The tensile strength retention rate of recycled glass fibers is only 55%-62%, and the reuse value of recycled fibers is extremely low. Second, high-temperature long-term pyrolysis consumes a lot of energy and produces a large amount of pyrolysis tar byproducts, which easily causes coking and blockage of pyrolysis equipment, making it impossible to meet the needs of continuous industrial processing. Third, simple high-temperature pyrolysis relies on heat to forcibly break the resin cross-linking bonds, resulting in high reaction activation energy and poor reaction controllability. The resin macromolecular chain segments are prone to secondary cross-linking and carbonization, resulting in a large amount of residual carbon on the fiber surface, which seriously affects the cleanliness and reusability of recycled glass fibers.

[0004] Some existing improved technologies attempt to assist pyrolysis with a single catalyst, but relying solely on a single catalytic component cannot simultaneously achieve the dual effects of reducing the reaction activation energy and inhibiting secondary coking. They generally suffer from defects such as limited reduction in activation energy, incomplete resin decomposition, severe residual carbon, and still significant fiber damage, and still cannot achieve the effect of low-temperature, high-efficiency, low-damage, and high-cleanliness wind turbine blade dissociation and recycling.

[0005] To address this issue, we propose a low-temperature pyrolysis method for wind turbine blades that reduces activation energy and achieves efficient dissociation. Summary of the Invention

[0006] To address one of the problems existing in the prior art, this invention provides a low-temperature pyrolysis method for wind turbine blades that reduces activation energy, solving the problems of high activation energy, high temperature, significant fiber damage, severe coking, and low recovery rate in traditional pyrolysis.

[0007] To achieve the above objectives, the present invention employs a low-temperature pyrolysis and high-efficiency dissociation method for wind turbine blades that reduces activation energy, comprising: S1. Pre-treatment process: Remove the metal embedded parts and bolt assemblies of the retired wind turbine blades, shear and crush the retired wind turbine blades and screen them to obtain wind turbine blade fragments with a size of 12mm-18mm; control the material temperature during the crushing process to not exceed 55℃, dry the screened wind turbine blade fragments at a constant temperature of 105℃ for 120min, and cool them to room temperature for later use. S2. Catalytic activation impregnation process: Prepare a catalytic activation treatment solution, which is composed of a modified hydroxyapatite solid catalyst, a composite phosphorus-containing activation aid, and an anhydrous ethanol dispersion medium; the composite phosphorus-containing activation aid is composed of ammonium polyphosphate and diphenyl phosphite in a mass ratio of 2.3:1; completely immerse the pretreated wind turbine blade fragments in the catalytic activation treatment solution, vacuum impregnate for 45 minutes under a vacuum degree of -0.075MPa, remove the material and allow it to evaporate naturally to remove the anhydrous ethanol, thus obtaining the wind turbine blade material to be treated with the catalytic activation system. S3. Preheating and exhaust process: The material to be processed for wind turbine blades is spread out with a thickness controlled at 35mm-45mm and placed in a closed fixed bed pyrolysis furnace; high-purity nitrogen gas with a purity of 99.99% is continuously purged for 25 minutes to replace the air in the furnace chamber; the temperature is increased to 240℃ at a heating rate of 2.5℃ / min and held at a constant temperature for 60 minutes to complete the pre-degassing and pre-activation of the material. S4. Segmented gradient low-temperature pyrolysis dissociation process: Maintaining the state of high-purity nitrogen gas introduction, the pyrolysis is carried out in segments with gradient temperature increase; the first pyrolysis stage is heated to 345℃ at a heating rate of 3.2℃ / min and held at a constant temperature for 75min-90min; the second pyrolysis stage is heated to 410℃ at a heating rate of 1.8℃ / min and held at a constant temperature for 95min-110min. S5. In-situ carbon removal process in the furnace: Stop the introduction of high-purity nitrogen and introduce a low-oxygen mixed atmosphere with an oxygen volume ratio of 3.2%-4.5% to maintain the furnace temperature at 410℃. Purge in situ for 35-48 minutes to remove carbon residue adhering to the glass fiber surface. After purging, introduce high-purity nitrogen again to replace the low-oxygen atmosphere in the furnace. S6. Inert atmosphere cooling discharge process: Maintain high-purity nitrogen protection, cool down at a rate of 3℃ / min, and discharge the material when the furnace temperature drops below 55℃. Screen and recover the recycled glass fiber and modified hydroxyapatite solid catalyst.

[0008] As a further optimization of the above scheme, the particle size of the modified hydroxyapatite solid catalyst is 25μm-45μm, and the inner wall of the catalyst channel is loaded with dual active sites of divalent manganese ions and lanthanum ions in situ, and a hierarchical mesoporous-macroporous composite channel structure is constructed inside the catalyst.

[0009] As a further optimization of the above scheme, in the catalytic activation treatment liquid, the modified hydroxyapatite solid catalyst accounts for 11% by mass, the composite phosphorus-containing activation aid accounts for 6% by mass, and the remainder is anhydrous ethanol dispersion medium.

[0010] As a further optimization of the above scheme, the flow rates of both the low-oxygen mixed atmosphere and the high-purity nitrogen gas are controlled at 55 mL / min.

[0011] As a further optimization of the above scheme, the modified hydroxyapatite solid catalyst can be recycled and reused after cleaning and activation.

[0012] As a further optimization of the above scheme, after treatment by this method, the apparent activation energy of epoxy resin matrix pyrolysis is reduced to 88kJ / mol-94kJ / mol, the resin matrix decomposition rate is ≥94.8%, the tensile strength retention rate of recycled glass fiber is ≥84%, and the carbon residue rate on the fiber surface is ≤1.8%.

[0013] The present invention provides a low-temperature pyrolysis and high-efficiency dissociation method for wind turbine blades that reduces activation energy, which has the following beneficial effects: The modified hydroxyapatite solid catalyst of this invention has divalent manganese ions and lanthanum ions loaded inside its pores as active sites. The modified hydroxyapatite solid catalyst selectively catalyzes the cleavage of CN bonds and CO ether bonds in the epoxy resin crosslinking network by relying on the acid-base active sites on its surface, thereby reducing the chemical bond cleavage reaction barrier. The composite phosphorus-containing activating agent decomposes upon heating to release phosphorus-containing free radical active intermediates. The phosphorus-containing free radical active intermediates capture the macromolecular free radicals generated during the resin pyrolysis process, inhibiting the secondary crosslinking of macromolecular chain segments to form dense pyrolysis residues. This invention integrates a preheating and exhaust process, a segmented gradient heating pyrolysis program, and a low-oxygen in-situ residual carbon removal process. The preheating and exhaust process pre-activates and degasses the material in advance, avoiding the concentrated release of large amounts of volatiles instantaneously. The segmented gradient heating program matches the gradual depolymerization reaction kinetics of the resin matrix, avoiding local overheating and coking caused by excessively rapid heating rates. The low-oxygen in-situ residual carbon removal process does not require material removal; residual carbon removal is completed directly inside the furnace, without damaging the glass fiber structure throughout the process.

[0014] Specific embodiments of the present invention are disclosed in detail with reference to the following description and accompanying drawings, indicating how the principles of the present invention can be adopted. It should be understood that the embodiments of the present invention are not limited in scope as a result, and that the embodiments of the present invention include many changes, modifications and equivalents within the spirit and scope of the appended claims. Attached Figure Description

[0015] Figure 1 This is a schematic diagram of the steps of the low-temperature pyrolysis high-efficiency dissociation method for wind turbine blades to reduce activation energy according to the present invention. Detailed Implementation

[0016] Please refer to the instruction manual appendix. Figure 1 The present invention provides a technical solution: a low-temperature pyrolysis and high-efficiency dissociation method for wind turbine blades that reduces activation energy.

[0017] Under conventional inert atmosphere pyrolysis conditions, the apparent activation energy of epoxy resin matrix pyrolysis is between 142 kJ / mol and 168 kJ / mol. Conventional pyrolysis requires a pyrolysis temperature of 520℃-580℃ and a holding time of 120min-180min to achieve complete decomposition and dissociation of the resin matrix. High temperature conditions can cause crystallization etching and microcrack propagation on the glass fiber surface, and the tensile strength retention rate of recycled glass fiber is only maintained at 55%-62%. At the same time, the overall process has high energy consumption, a large amount of tar by-products are produced during pyrolysis, and equipment coking and blockage are prominent problems, making it difficult to carry out continuous industrial processing.

[0018] This invention employs a composite catalytic activation system coupled with a segmented gradient temperature-controlled pyrolysis process. The composite catalytic activation system consists of a modified hydroxyapatite solid catalyst and a composite phosphorus-containing activation aid. The modified hydroxyapatite solid catalyst has a hierarchical mesoporous-macroporous channel structure, with divalent manganese ions and lanthanum ions loaded in situ on the inner walls of the channels. The modified hydroxyapatite solid catalyst can selectively attack the CN bonds and CO ether bonds within the epoxy resin crosslinking network, reducing the reaction barrier required for chemical bond breaking. The composite phosphorus-containing activation aid is obtained by compounding ammonium polyphosphate and diphenyl phosphite in a specific mass ratio. Upon thermal decomposition, the composite phosphorus-containing activation aid generates phosphorus-containing free radical active intermediates. These phosphorus-containing free radical active intermediates can capture the macromolecular free radicals generated by the pyrolysis of epoxy resin macromolecular segments, inhibiting the re-crosslinking, carbonization, and coking behavior of macromolecular segments. The synergistic effect of the two reduces the apparent activation energy of the epoxy resin matrix pyrolysis to 83 kJ / mol-102 kJ / mol, achieving full dissociation of the resin matrix under low-temperature conditions.

[0019] This invention consists of six processes: pretreatment, catalytic activation and impregnation, preheating and exhaust, segmented gradient low-temperature pyrolysis and dissociation, in-situ residual carbon removal in the furnace, and inert atmosphere cooling and discharge. All six processes are completed inside a closed intermittent fixed-bed pyrolysis reactor. The closed intermittent fixed-bed pyrolysis reactor is equipped with a programmed temperature control system, an inert atmosphere supply system, a flue gas condensation and collection system, and an in-furnace oscillating material distribution mechanism. The closed intermittent fixed-bed pyrolysis reactor can achieve closed-loop control of the internal atmosphere, heating rate, holding temperature, and holding time.

[0020] This invention includes the following steps: Step 1, Pre-treatment process: Remove the metal embedded parts and bolt assemblies from the surface of the retired wind turbine blades. Use a shearing crusher to shear and crush the retired wind turbine blades. After crushing, screen to obtain wind turbine blade fragments with a size of 12mm-18mm. Use a forced-air cooling method to control the material temperature during the shearing and crushing process to not exceed 55℃, to avoid premature thermal aging and decomposition of local resin caused by shear friction heat. After screening, transport the wind turbine blade fragments to a hot air drying box for constant temperature drying treatment. The constant temperature drying treatment temperature is set to 105℃ and the constant temperature drying treatment time is set to 120min to remove adsorbed free moisture inside the wind turbine blade fragments. After drying, take out the material and let it cool naturally to room temperature for later use.

[0021] Step 2, Catalytic Activation Impregnation Process: The catalytic activation treatment solution is prepared by mixing a modified hydroxyapatite solid catalyst, a composite phosphorus-containing activation aid, and an anhydrous ethanol dispersion medium. The particle size of the modified hydroxyapatite solid catalyst is controlled to be 25μm-45μm. The mass ratio of ammonium polyphosphate to diphenyl phosphite in the composite phosphorus-containing activation aid is 2.3:1. The modified hydroxyapatite solid catalyst accounts for 11% of the total mass fraction of the catalytic activation treatment solution, the composite phosphorus-containing activation aid accounts for 6%, and the remainder is dispersed in anhydrous ethanol. Medium; the pretreated wind turbine blade fragments are completely immersed in the catalytic activation treatment liquid, and vacuum impregnation is carried out at room temperature. The vacuum degree of the vacuum impregnation treatment is maintained at -0.075MPa, and the vacuum impregnation treatment time is set to 45min. After the vacuum impregnation is completed, the wind turbine blade fragments are taken out and placed in a ventilated environment to naturally evaporate and remove the anhydrous ethanol dispersion medium, so that the modified hydroxyapatite solid catalyst and the composite phosphorus-containing activation aid are uniformly attached and penetrated into the gaps of the wind turbine blade fragment matrix, thus obtaining the wind turbine blade material to be treated with the catalytic activation system.

[0022] Step 3, Preheating and Exhausting Process: The material to be processed, including the wind turbine blades from the catalytic activation system, is laid flat on the material tray inside the closed intermittent fixed-bed pyrolysis reactor. The material thickness is controlled to be 35mm-45mm. The furnace door is closed, and the inert atmosphere supply system is turned on to continuously introduce high-purity nitrogen into the furnace cavity. The purity of the high-purity nitrogen gas is greater than or equal to 99.99%, and the flow rate is set to 55mL / min. High-purity nitrogen is continuously introduced for purging for 25 minutes to completely replace and remove residual air from the furnace cavity. After purging, the high-purity nitrogen is maintained at a constant level. Continuing to supply power, the programmable heating control system is activated to execute the preheating and exhaust stage program. The heating rate during the preheating and exhaust stage is set to 2.5℃ / min, raising the furnace temperature from room temperature to 240℃. After reaching 240℃, the temperature is maintained at a constant level for 60 minutes. The main function of the preheating and exhaust stage is to further remove residual ethanol and trace amounts of adsorbed water from the material. At the same time, the composite phosphorus-containing activating agent begins to initially release active phosphorus-containing intermediates to preactivate the epoxy resin crosslinking network, thus preventing a sudden burst of volatile components from the material during the subsequent rapid heating process, which could cause drastic fluctuations in the furnace pressure.

[0023] Step 4, Segmented Gradient Low-Temperature Pyrolysis and Dissociation Process: After the preheating and exhaust process is completed, without changing the flow rate of high-purity nitrogen into the furnace cavity, a segmented gradient heating program is executed; the heating rate of the first pyrolysis stage is set to 3.2℃ / min, and the furnace cavity temperature is raised from 240℃ to 345℃, and then held at 345℃ for 90min; under the conditions of the first pyrolysis stage, the active sites on the surface of the modified hydroxyapatite solid catalyst fully exert their catalytic bond-breaking effect, and a large number of CN bonds and CO ether bonds in the three-dimensional cross-linked network of epoxy resin break, and the epoxy resin macromolecular cross-linked network gradually depolymerizes into medium molecular weight segment products; the heating rate of the second pyrolysis stage is set to 1. The furnace temperature is increased from 345℃ to 410℃ at a rate of 8℃ / min, and then held at 410℃ for 110 minutes. The second pyrolysis stage is the dissociation stage of the resin matrix. The composite phosphorus-containing activating agent releases a large amount of phosphorus-containing free radical active intermediates. The phosphorus-containing free radical active intermediates combine with the macromolecular free radicals generated by the pyrolysis of the resin, inhibiting the re-crosslinking of macromolecular chain segments to form dense char residues. Most of the epoxy resin matrix is ​​converted into volatile pyrolysis oil and gas products, realizing the interface dissociation between the resin matrix and glass fiber. The pyrolysis oil and gas products generated during the pyrolysis process are condensed and separated by the flue gas condensation collection system, and the pyrolysis oil liquid phase products and non-condensable pyrolysis gas products are collected separately.

[0024] Step 5, In-situ Residual Carbon Removal Process: After the segmented gradient low-temperature pyrolysis dissociation process is completed, the introduction of high-purity nitrogen into the furnace cavity is stopped, and the gas path is switched to introduce a low-oxygen concentration mixed atmosphere into the furnace cavity. The low-oxygen concentration mixed atmosphere is prepared by mixing high-purity nitrogen and air, with an oxygen volume ratio of 4.5% and an introduction flow rate of 55 mL / min. The furnace cavity temperature is maintained at 410℃, and the constant temperature in-situ purging treatment time is set to 35 min. The low-oxygen concentration weak oxidizing atmosphere is used to carry out in-situ oxidation removal of a small amount of pyrolysis residual carbon adhering to the glass fiber surface. The oxygen content and treatment temperature of the atmosphere are controlled to avoid oxidation and etching damage to the glass fiber body caused by high oxygen conditions. After the in-situ residual carbon removal process is completed, the gas path is switched again to resume the introduction of high-purity nitrogen to completely replace and discharge the residual low-oxygen mixed atmosphere inside the furnace cavity.

[0025] Step 6, inert atmosphere cooling and discharge process: Maintain high-purity nitrogen gas continuously entering the furnace cavity, stop heating, and program the temperature to drop under sealed conditions at a rate of 3℃ / min. After the overall temperature inside the furnace cavity drops below 55℃, open the furnace door, remove the solid product from the material tray, and screen and separate the modified hydroxyapatite solid catalyst particles and clean recycled glass fiber. The modified hydroxyapatite solid catalyst can be recycled and used in subsequent batches of processes after simple cleaning and activation.

[0026] Example 1 This embodiment is a low-temperature pyrolysis and high-efficiency dissociation method for wind turbine blades that reduces activation energy, implemented according to the process steps of this invention; Step 1, Pre-treatment process: Remove the metal embedded parts of the decommissioned wind turbine blades, and shear, crush and screen to obtain wind turbine blade fragments with a size of 12mm-18mm; the material temperature is controlled not to exceed 55℃ throughout the shearing and crushing process; dry with hot air at 105℃ for 120 minutes, and then cool naturally to room temperature for later use.

[0027] Step 2, Catalytic Activation Impregnation Process: Prepare the catalytic activation treatment solution; the modified hydroxyapatite solid catalyst has a particle size of 25μm-45μm, and the inner wall of the pores of the modified hydroxyapatite solid catalyst is loaded with divalent manganese ions and lanthanum ions as active sites; the composite phosphorus-containing activation aid ammonium polyphosphate and diphenyl phosphite have a mass ratio of 2.3:1; the modified hydroxyapatite solid catalyst accounts for 11% of the total mass fraction of the catalytic activation treatment solution, the composite phosphorus-containing activation aid accounts for 6% of the total mass fraction of the catalytic activation treatment solution, and the remaining components are anhydrous ethanol dispersion medium; the wind turbine blade fragments are completely immersed in the catalytic activation treatment solution, vacuum impregnated at a vacuum degree of -0.075MPa, and the vacuum impregnation time is 45min; after impregnation, the material is removed, and the anhydrous ethanol dispersion medium is removed by ventilation to obtain the wind turbine blade material to be treated with the catalytic activation system.

[0028] Step 3, Preheating and Exhausting Process: The wind turbine blade material to be treated, supported by the catalytic activation system, is laid flat on the material tray of the closed intermittent fixed bed pyrolysis reactor, with a material thickness of 38mm; the furnace door is closed, and high-purity nitrogen of 99.99% purity is introduced at a flow rate of 55mL / min, and the furnace cavity is continuously purged for 25min to replace the air inside; after purging, nitrogen is continuously introduced, and the heating rate during the preheating and exhausting stage is 2.5℃ / min, raising the temperature to 240℃, and maintaining the temperature at 240℃ for 60min.

[0029] Step 4, segmented gradient low-temperature pyrolysis dissociation process: maintain a high-purity nitrogen flow rate of 55 mL / min; the heating rate of the first pyrolysis section is 3.2℃ / min, the furnace temperature rises from 240℃ to 345℃, and is held at 345℃ for 90 min; the heating rate of the second pyrolysis section is 1.8℃ / min, the furnace temperature rises from 345℃ to 410℃, and is held at 410℃ for 110 min; the pyrolysis oil and gas are continuously discharged to the flue gas condensation and collection system to complete product collection.

[0030] Step 5, in-situ carbon removal process in the furnace: Stop the introduction of high-purity nitrogen and switch to the introduction of a low-oxygen concentration mixed atmosphere. The oxygen volume ratio of the low-oxygen concentration mixed atmosphere is 4.5%, and the gas flow rate is 55 mL / min. The furnace temperature is maintained at 410℃, and the constant temperature in-situ purging treatment lasts for 35 min. After the treatment is completed, high-purity nitrogen is introduced again to replace the low-oxygen mixed atmosphere inside the furnace.

[0031] Step 6, inert atmosphere cooling and discharge process: Maintain the flow of high-purity nitrogen, stop heating, and cool down at a rate of 3℃ / min. After the overall temperature of the furnace cavity is cooled to 52℃, open the furnace door to discharge the material; screen and recover the modified hydroxyapatite solid catalyst and recycled glass fiber.

[0032] The test data results of this embodiment are as follows: apparent activation energy of epoxy resin matrix pyrolysis 91kJ / mol; resin matrix decomposition rate 97.4%; residual carbon rate on the surface of recycled glass fiber 1.23%; tensile strength retention rate of recycled glass fiber 84.7%.

[0033] Example 2 This embodiment is a low-temperature pyrolysis high-efficiency dissociation method for wind turbine blades to reduce activation energy, implemented according to the process steps of this invention; the composition ratio of the catalytic activation treatment liquid and the basic operation process of each step are consistent with those in Example 1, the difference being that the process parameters of the segmented gradient low-temperature pyrolysis dissociation step are adjusted: the heating rate of the first pyrolysis stage is 3.2℃ / min, and the furnace temperature is raised from 240℃ to 345℃ and then kept at a constant temperature for 75min; the heating rate of the second pyrolysis stage is 1.8℃ / min, and the furnace temperature is raised from 345℃ to 410℃ and then kept at a constant temperature for 95min; all process parameters of the remaining steps are the same as those in Example 1.

[0034] Step 1, Pre-treatment process: Remove the metal embedded parts of the decommissioned wind turbine blades, and shear, crush and screen to obtain wind turbine blade fragments with a size of 12mm-18mm; the material temperature is controlled not to exceed 55℃ throughout the shearing and crushing process; dry with hot air at 105℃ for 120 minutes, and then cool naturally to room temperature for later use.

[0035] Step 2, Catalytic Activation Impregnation Process: Prepare the catalytic activation treatment solution; the modified hydroxyapatite solid catalyst has a particle size of 25μm-45μm, and the inner wall of the pores of the modified hydroxyapatite solid catalyst is loaded with divalent manganese ions and lanthanum ions as active sites; the composite phosphorus-containing activation aid ammonium polyphosphate and diphenyl phosphite have a mass ratio of 2.3:1; the modified hydroxyapatite solid catalyst accounts for 11% of the total mass fraction of the catalytic activation treatment solution, the composite phosphorus-containing activation aid accounts for 6% of the total mass fraction of the catalytic activation treatment solution, and the remaining components are anhydrous ethanol dispersion medium; the wind turbine blade fragments are completely immersed in the catalytic activation treatment solution, vacuum impregnated at a vacuum degree of -0.075MPa, and the vacuum impregnation time is 45min; after impregnation, the material is removed, and the anhydrous ethanol dispersion medium is removed by ventilation to obtain the wind turbine blade material to be treated with the catalytic activation system.

[0036] Step 3, Preheating and Exhausting Process: The wind turbine blade material to be treated, supported by the catalytic activation system, is laid flat on the material tray of the closed intermittent fixed bed pyrolysis reactor, with a material thickness of 38mm; the furnace door is closed, and high-purity nitrogen of 99.99% purity is introduced at a flow rate of 55mL / min, and the furnace cavity is continuously purged for 25min to replace the air inside; after purging, nitrogen is continuously introduced, and the heating rate during the preheating and exhausting stage is 2.5℃ / min, raising the temperature to 240℃, and maintaining the temperature at 240℃ for 60min.

[0037] Step 4, segmented gradient low-temperature pyrolysis dissociation process: maintain a high-purity nitrogen flow rate of 55 mL / min; the heating rate of the first pyrolysis section is 3.2℃ / min, the furnace temperature rises from 240℃ to 345℃, and is held at 345℃ for 75 min; the heating rate of the second pyrolysis section is 1.8℃ / min, the furnace temperature rises from 345℃ to 410℃, and is held at 410℃ for 95 min; the pyrolysis oil and gas are continuously discharged to the flue gas condensation and collection system to complete product collection.

[0038] Step 5, in-situ carbon removal process in the furnace: Stop the introduction of high-purity nitrogen and switch to the introduction of a low-oxygen concentration mixed atmosphere. The oxygen volume ratio of the low-oxygen concentration mixed atmosphere is 4.5%, and the gas flow rate is 55 mL / min. The furnace temperature is maintained at 410℃, and the constant temperature in-situ purging treatment lasts for 35 min. After the treatment is completed, high-purity nitrogen is introduced again to replace the low-oxygen mixed atmosphere inside the furnace.

[0039] Step 6, inert atmosphere cooling and discharge process: Maintain the flow of high-purity nitrogen, stop heating, cool down at a rate of 3℃ / min, and open the furnace door to discharge the material after the overall temperature of the furnace cavity has cooled to 51℃; screen and recover the modified hydroxyapatite solid catalyst and recycled glass fiber.

[0040] The test data results of this embodiment are as follows: apparent activation energy of epoxy resin matrix pyrolysis 94 kJ / mol; resin matrix decomposition rate 94.8%; residual char rate on the surface of recycled glass fiber 1.76%; tensile strength retention rate of recycled glass fiber 86.2%.

[0041] Example 3 This embodiment is a low-temperature pyrolysis and high-efficiency dissociation method for wind turbine blades with reduced activation energy, implemented according to the process steps of this invention; the composition ratio of the catalytic activation treatment liquid and the basic operation process of each step are consistent with those of Embodiment 1, the difference being that the process parameters of the in-situ residual carbon removal process in the furnace are adjusted: the oxygen volume ratio of the low oxygen concentration mixed atmosphere is adjusted to 3.2%, and the constant temperature in-situ purging treatment time is adjusted to 48 min; all process parameters of the remaining steps are the same as those of Embodiment 1.

[0042] Step 1, Pre-treatment process: Remove the metal embedded parts of the decommissioned wind turbine blades, and shear, crush and screen to obtain wind turbine blade fragments with a size of 12mm-18mm; the material temperature is controlled not to exceed 55℃ throughout the shearing and crushing process; dry with hot air at 105℃ for 120 minutes, and then cool naturally to room temperature for later use.

[0043] Step 2, Catalytic Activation Impregnation Process: Prepare the catalytic activation treatment solution; the modified hydroxyapatite solid catalyst particles have a diameter of 25-45 μm, and the inner wall of the modified hydroxyapatite solid catalyst pores is loaded with divalent manganese ions and lanthanum ions as active sites; the composite phosphorus-containing activation aid ammonium polyphosphate and diphenyl phosphite have a mass ratio of 2.3:1; the modified hydroxyapatite solid catalyst accounts for 11% of the total mass fraction of the catalytic activation treatment solution, the composite phosphorus-containing activation aid accounts for 6% of the total mass fraction of the catalytic activation treatment solution, and the remaining components are anhydrous ethanol dispersion medium; the wind turbine blade fragments are completely immersed in the catalytic activation treatment solution, vacuum impregnated at a vacuum degree of -0.075 MPa, and the vacuum impregnation time is 45 min; after impregnation, the material is removed, and the anhydrous ethanol dispersion medium is removed by ventilation to obtain the wind turbine blade material to be treated with the catalytic activation system.

[0044] Step 3, Preheating and Exhausting Process: The wind turbine blade material to be treated, supported by the catalytic activation system, is laid flat on the material tray of the closed intermittent fixed bed pyrolysis reactor, with a material thickness of 38mm; the furnace door is closed, and high-purity nitrogen of 99.99% purity is introduced at a flow rate of 55mL / min, and the furnace cavity is continuously purged for 25min to replace the air inside; after purging, nitrogen is continuously introduced, and the heating rate during the preheating and exhausting stage is 2.5℃ / min, raising the temperature to 240℃, and maintaining the temperature at 240℃ for 60min.

[0045] Step 4, segmented gradient low-temperature pyrolysis dissociation process: maintain a high-purity nitrogen flow rate of 55 mL / min; the heating rate of the first pyrolysis section is 3.2℃ / min, the furnace temperature rises from 240℃ to 345℃, and is held at 345℃ for 90 min; the heating rate of the second pyrolysis section is 1.8℃ / min, the furnace temperature rises from 345℃ to 410℃, and is held at 410℃ for 110 min; the pyrolysis oil and gas are continuously discharged to the flue gas condensation and collection system to complete product collection.

[0046] Step 5, in-situ carbon removal process in the furnace: Stop the introduction of high-purity nitrogen and switch to the introduction of a low-oxygen concentration mixed atmosphere. The oxygen volume ratio of the low-oxygen concentration mixed atmosphere is 3.2%, and the gas flow rate is 55 mL / min. The furnace temperature is maintained at 410℃, and the constant temperature in-situ purging treatment lasts for 48 min. After the treatment is completed, high-purity nitrogen is introduced again to replace the low-oxygen mixed atmosphere inside the furnace.

[0047] Step 6, inert atmosphere cooling and discharge process: Maintain the flow of high-purity nitrogen, stop heating, cool down at a rate of 3℃ / min, and open the furnace door to discharge the material after the overall temperature of the furnace cavity has cooled to 53℃; screen and recover the modified hydroxyapatite solid catalyst and recycled glass fiber.

[0048] The test data results of this embodiment are as follows: apparent activation energy of epoxy resin matrix pyrolysis 88kJ / mol; resin matrix decomposition rate 96.1%; residual carbon rate on the surface of recycled glass fiber 1.41%; tensile strength retention rate of recycled glass fiber 85.3%.

[0049] Comparative Example 1 This comparative example uses the traditional inert atmosphere pyrolysis process for wind turbine blades to treat the same batch of wind turbine blade fragments; no modified hydroxyapatite solid catalyst or composite phosphorus-containing activating agent is added; the pretreated wind turbine blade fragments are directly placed into a closed intermittent fixed bed pyrolysis reactor; under a high-purity nitrogen protective atmosphere, the temperature is increased to 540℃ at a rate of 5℃ / min, and held at 540℃ for 150min; the material is then cooled and discharged under an inert atmosphere.

[0050] Comparative Example 1 test data results: apparent activation energy of epoxy resin matrix pyrolysis 157kJ / mol; resin matrix decomposition rate 95.2%; residual carbon rate on recycled glass fiber surface 2.87%; tensile strength retention rate of recycled glass fiber 58.4%.

[0051] Comparative Example 2 This comparative example omits the composite phosphorus-containing activating agent and uses only a modified hydroxyapatite solid catalyst for vacuum impregnation treatment. All other process parameters are completely consistent with those in Example 1.

[0052] Comparative Example 2 test data results: apparent activation energy of epoxy resin matrix pyrolysis 124kJ / mol; resin matrix decomposition rate 87.3%; char residue rate on recycled glass fiber surface 4.12%; tensile strength retention rate of recycled glass fiber 76.1%.

[0053] A comparison of the experimental data from Examples 1 to 3 and Comparative Examples 1 to 2 shows that: Comparative Example 1, using the traditional pyrolysis process, requires a temperature of 540℃ to achieve resin matrix decomposition and dissociation, with an apparent activation energy as high as 157 kJ / mol. This high-temperature environment causes significant thermal damage to the glass fiber matrix, resulting in a tensile strength retention rate of only 58.4% for the regenerated glass fiber. Comparative Example 2 uses only a modified hydroxyapatite solid catalyst, lacking the synergistic effect of a composite phosphorus-containing activating agent. The reduction in activation energy is limited, and the re-crosslinking and coking of macromolecular chain segments during pyrolysis is severe, leading to a decrease in resin matrix decomposition rate and a significant increase in residual carbon on the fiber surface. Examples 1 to 3 of this invention use modified hydroxyapatite... A composite catalytic activation system is formed by combining apatite solid catalyst with a composite phosphorus-containing activating agent. The two produce a synergistic effect, reducing the apparent activation energy of epoxy resin matrix pyrolysis to the range of 88kJ / mol-94kJ / mol. Efficient dissociation of the resin matrix can be achieved at a relatively low pyrolysis temperature of 410℃, with the resin matrix decomposition rate reaching up to 97.4%. The residual carbon rate on the surface of recycled glass fiber is controlled within 1.8%, and the tensile strength retention rate of recycled glass fiber can be stably maintained above 84%. Compared with existing traditional pyrolysis technology, the pyrolysis treatment temperature is significantly reduced, the mechanical properties of recycled glass fiber are significantly preserved, and the output of pyrolysis tar byproducts is significantly reduced, alleviating the problem of coking and clogging in pyrolysis equipment.

Claims

1. A low-temperature pyrolysis and high-efficiency dissociation method for wind turbine blades to reduce activation energy, characterized in that, include: S1. Pre-treatment process: Remove the metal embedded parts and bolt assemblies of the retired wind turbine blades, shear and crush the retired wind turbine blades and screen them to obtain wind turbine blade fragments with a size of 12mm-18mm; control the material temperature during the crushing process to not exceed 55℃, dry the screened wind turbine blade fragments at a constant temperature of 105℃ for 120min, and cool them to room temperature for later use. S2. Catalytic activation impregnation process: Prepare a catalytic activation treatment solution, which is composed of a modified hydroxyapatite solid catalyst, a composite phosphorus-containing activation aid, and an anhydrous ethanol dispersion medium; the composite phosphorus-containing activation aid is composed of ammonium polyphosphate and diphenyl phosphite in a mass ratio of 2.3:1; completely immerse the pretreated wind turbine blade fragments in the catalytic activation treatment solution, vacuum impregnate for 45 minutes under a vacuum degree of -0.075MPa, remove the material and allow it to evaporate naturally to remove the anhydrous ethanol, thus obtaining the wind turbine blade material to be treated with the catalytic activation system. S3. Preheating and exhaust process: The material to be processed for wind turbine blades is spread out with a thickness controlled at 35mm-45mm and placed in a closed fixed bed pyrolysis furnace; high-purity nitrogen gas with a purity of 99.99% is continuously purged for 25 minutes to replace the air in the furnace chamber; the temperature is increased to 240℃ at a heating rate of 2.5℃ / min and held at a constant temperature for 60 minutes to complete the pre-degassing and pre-activation of the material. S4. Segmented gradient low-temperature pyrolysis dissociation process: Maintaining the state of high-purity nitrogen gas introduction, the pyrolysis is carried out in segments with gradient temperature increase; the first pyrolysis stage is heated to 345℃ at a heating rate of 3.2℃ / min and held at a constant temperature for 75min-90min; the second pyrolysis stage is heated to 410℃ at a heating rate of 1.8℃ / min and held at a constant temperature for 95min-110min. S5. In-situ carbon removal process in the furnace: Stop the introduction of high-purity nitrogen and introduce a low-oxygen mixed atmosphere with an oxygen volume ratio of 3.2%-4.5% to maintain the furnace temperature at 410℃. Purge in situ for 35-48 minutes to remove carbon residue adhering to the glass fiber surface. After purging, introduce high-purity nitrogen again to replace the low-oxygen atmosphere in the furnace. S6. Inert atmosphere cooling discharge process: Maintain high-purity nitrogen protection, cool down at a rate of 3℃ / min, and discharge the material when the furnace temperature drops below 55℃. Screen and recover the recycled glass fiber and modified hydroxyapatite solid catalyst.

2. The method for efficient dissociation of wind turbine blades by low-temperature pyrolysis with reduced activation energy according to claim 1, characterized in that: The modified hydroxyapatite solid catalyst has a particle size of 25μm-45μm, and the inner wall of the catalyst channel is loaded with dual active sites of divalent manganese ions and lanthanum ions in situ. The catalyst has a hierarchical mesoporous-macroporous composite channel structure.

3. The method for efficient dissociation of wind turbine blades by low-temperature pyrolysis with reduced activation energy according to claim 1, characterized in that: In the catalytic activation treatment solution, the modified hydroxyapatite solid catalyst accounts for 11% by mass, the composite phosphorus-containing activation aid accounts for 6% by mass, and the remainder is anhydrous ethanol dispersion medium.

4. The method for efficient dissociation of wind turbine blades by low-temperature pyrolysis to reduce activation energy according to claim 1, characterized in that: The flow rates of both the low-oxygen mixed atmosphere and the high-purity nitrogen gas were controlled at 55 mL / min.

5. The method for efficient dissociation of wind turbine blades by low-temperature pyrolysis to reduce activation energy according to claim 1, characterized in that: The modified hydroxyapatite solid catalyst is recycled and reused after being cleaned and activated.

6. The method for efficient dissociation of wind turbine blades by low-temperature pyrolysis to reduce activation energy according to claim 1, characterized in that: After treatment by this method, the apparent activation energy of epoxy resin matrix pyrolysis is reduced to 88kJ / mol-94kJ / mol, the resin matrix decomposition rate is ≥94.8%, the tensile strength retention rate of recycled glass fiber is ≥84%, and the carbon residue rate on the fiber surface is ≤1.8%.